Jumlah Uang Beredar, Nilai Tukar Perdagangan Luar Negeri Dan Inflasi Di Indonesia - Edalmen, Edalmen (Jurnal Ekonomi, 2019)
This study aims to determine the effect of the money supply and the exchange rate of foreign trade on inflation in Indonesia. This study concludes that the money supply has a positive and significant influence on inflation. The foreign trade exchange rate has a negative relationship to inflation, but the effect is not statistically significant. For further research it is recommended to add other independent variables that are related and take into account the exchange rate of foreign trade according to the group of goods.